Chemical oxygen demand removal from electroplating wastewater by purified and polymer functionalized carbon nanotubes adsorbents - M.T. Bankole; A.S. Abdulkareem; J.O. Tijani; S.S. Ochigbo; A.S. Afolabi; W.D. Roos (Water Resources and Industry, 2017)
This study investigated the removal of chemical oxygen demand (COD) from electroplating industry wastewater via batch adsorption by purified and polymers functionalized carbon nanotubes (CNTs) as nano-adsorbents. Bimetallic Fe-Co supported on CaCO3 was utilized to produce multi-walled carbon nanotubes (MWCNT) via the catalytic chemical vapor deposition (CCVD) technique. This was subsequently followed by the purification of the as-prepared MWCNTs by a mixture of HNO3 and H2SO4 in order to remove the support and metal particles. The purified MWCNTs was further functionalized using known mass of the following polymers: Amino polyethylene glycol (PEG), polyhydroxylbutyrate (PHB) and amino polyethylene glycol with polyhydroxylbutyrate (PEG-PHB). The purified (P-CNTs) and functionalized CNTs coded PEG-CNTs; PHB-CNTs, and PEG-PHB-CNTs were characterized by HRSEM, HRTEM-EDS, BET, XRD and XPS. The electroplating wastewater was subjected to physicochemical characterization before and after treatment with various prepared nano-adsorbents using standard methods. The adsorption process under the influence of contact time, adsorbent dosage and temperature was measured using the chemical oxygen demand (COD) as indicator parameter. The HRSEM/XRD/BET confirmed that the purified and polymer functionalized CNTs were homogeneously dispersed; highly graphitic in nature with fewer impurities and of high surface area (>145 m2/g). The order of maximum COD removal by the nano-adsorbents at equilibrium time of 70 min are as follows: PEG-CNTs (99.68%) > PHB-CNTs (97.89%) > P-CNTs (96.34%) > PEG/PHB-CNTs (95.42%). Equilibrium sorption data were better described by Freudlich isotherm with the correlation coefficient (R2>0.92) than Langmuir isotherm. The adsorption kinetics for COD removal from electroplating wastewater fitted well to the pseudo-second-order model with rate constant in the range of 4 × 10−5–1 × 10−4 (g mg−1 min−1). Thermodynamics analysis of the adsorption process revealed that the enthalpy (ΔH°) of the reaction was positive and endothermic in nature. The Gibbs free energy (ΔG°) was negative which showed the feasibility and spontaneity of adsorption process. The findings from this study support the potential use of PEG-functionalised CNTs as a nanoadsorbent to purify electroplating wastewater than others prepared sorbents.